2013
DOI: 10.1177/0009922813492882
|View full text |Cite
|
Sign up to set email alerts
|

Play and Video Effects on Mood and Procedure Behaviors in School-Aged Children Visiting the Pediatrician

Abstract: This study examines how different types of activities, including medical play, typical play, and videos, affect the mood and behaviors of children visiting a pediatric office. Seventy-two school-aged children visiting a pediatrician's office were randomly assigned to 1 of 4 groups: medical play, medical information video, typical play, and nonmedical information video control. Children completed a mood self-report measure and their behaviors were recorded during triage by nurses. The medical information video … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
18
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 9 publications
(18 citation statements)
references
References 11 publications
0
18
0
Order By: Relevance
“…Of the nine studies identified, four were quasi-experimental in design (Bloch & Toker, 2008; Brewer, Gleditsch, Syblik, Tietjens, & Vacik, 2006; Hatava et al, 2000; Zahr, 1998) and five were randomized controlled trials (Burns-Nader, Hernandez-Reif, & Thoma, 2013; Li, Lopez, & Lee, 2007; Li & Lopez, 2008; Wee, Chan, Cheung Li & Hong-Gu, 2014; Wolfer & Visintainer, 1975). …”
Section: Literature Reviewmentioning
confidence: 99%
See 4 more Smart Citations
“…Of the nine studies identified, four were quasi-experimental in design (Bloch & Toker, 2008; Brewer, Gleditsch, Syblik, Tietjens, & Vacik, 2006; Hatava et al, 2000; Zahr, 1998) and five were randomized controlled trials (Burns-Nader, Hernandez-Reif, & Thoma, 2013; Li, Lopez, & Lee, 2007; Li & Lopez, 2008; Wee, Chan, Cheung Li & Hong-Gu, 2014; Wolfer & Visintainer, 1975). …”
Section: Literature Reviewmentioning
confidence: 99%
“…The studies were culturally diverse with children from North America (Wolfer & Visintainer, 1975; Burns-Nader et al, 2013; Brewer et al, 2006), Israel (Bloch & Toker, 2008), Lebanon (Zahr, 1998), Sweden (Hatava et al, 2000), Singapore (Wee et al, 2014) and Hong Kong (Li et al, 2007; Li & Lopez, 2008) enrolled.…”
Section: Literature Reviewmentioning
confidence: 99%
See 3 more Smart Citations